EULAR recommendations for the reporting of ultrasound studies in rheumatic and musculoskeletal diseases (RMDs). Issue 7 (22nd January 2021) - Costantino, Félicie; Carmona, Loreto; Boers, Maarten; Backhaus, Marina; Balint, Peter V; Bruyn, George A; Christensen, Robin; Conaghan, Philip G; Ferreira, Ricardo J O; Garrido-Castro, Juan Luis; Guillemin, Francis; Hammer, Hilde Berner; et al.
Abstract : Objective: To produce European League Against Rheumatism (EULAR) recommendations for the reporting of ultrasound studies in rheumatic and musculoskeletal diseases (RMDs). Methods: Based on the literature reviews and expert opinion (through Delphi surveys), a taskforce of 23 members (12 experts in ultrasound in RMDs, 9 in methodology and biostatistics together with a patient research partner and a health professional in rheumatology) developed a checklist of items to be reported in every RMD study using ultrasound. This checklist was further refined by involving a panel of 79 external experts (musculoskeletal imaging experts, methodologists, journal editors), who evaluated its comprehensibility, feasibility and comprehensiveness. Agreement on each proposed item was assessed with an 11-point Likert scale, grading from 0 (total disagreement) to 10 (full agreement). Results: Two face-to-face meetings, as well as two Delphi rounds of voting, resulted in a final checklist of 23 items, including a glossary of terminology. Twenty-one of these were considered 'mandatory' items to be reported in every study (such as blinding, development of scoring systems, definition of target pathologies) and 2 'optional' to be reported only if applicable, such as possible confounding factors (ie, ambient conditions) or experience of the sonographers. Conclusion: An EULAR taskforce developed a checklist to ensure transparent and comprehensive reporting of aspects concerning research and procedures that need to be presented in studies using ultrasound in RMDs. This checklist, if widely adopted by authors and editors, will greatly improve the interpretability of study development and results, including the assessment of validity, generalisability and applicability.